2022
DOI: 10.1073/pnas.2206072119
|View full text |Cite
|
Sign up to set email alerts
|

Americans discount the effect of friction on voter turnout

Abstract: Whether or not someone turns out to vote depends on their beliefs (such as partisanship or sense of civic duty) and on friction —external barriers such as long travel distance to the polls. In this exploratory study, we tested whether people underestimate the effect of friction on turnout and overestimate the effect of beliefs. We surveyed a representative sample of eligible US voters before and after the 2020 election ( n = 1,280). Participants’ perceptions cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Finally, in a democracy, key individual decisions citizens make is through voting – and a crucial systemic challenge is to maximize turnout. Recent work (Mazar, Tomaino, Carmon, & Wood, 2022) has revealed that people dramatically underestimate the impact of “frictional” factors (e.g., long-distances to travel) on voter turnout. Citizens who are particularly prone to this bias are especially supportive of measures that would increase frictional effects.…”
Section: Toward An S-frame Behavioral Public Policymentioning
confidence: 99%
“…Finally, in a democracy, key individual decisions citizens make is through voting – and a crucial systemic challenge is to maximize turnout. Recent work (Mazar, Tomaino, Carmon, & Wood, 2022) has revealed that people dramatically underestimate the impact of “frictional” factors (e.g., long-distances to travel) on voter turnout. Citizens who are particularly prone to this bias are especially supportive of measures that would increase frictional effects.…”
Section: Toward An S-frame Behavioral Public Policymentioning
confidence: 99%
“…However, most MTO adult participants faced barriers to AVR since most of them do not own a car or driver’s license, despite moving to neighborhoods that necessitate driving as a means of transport ( 45 ). Studies show that not owning a car reduces voter turnout ( 46 ). These existing studies on AVR predict that the vouchers would reduce voter registration for those without driver’s licenses more so than those who have driver’s licenses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a democracy, key individual decisions citizens make is through voting---and a crucial systemic challenge is to maximize turn-out. Recent work (Mazar, Tomaino, Carmon & Wood, 2022) has revealed that people dramatically underestimate the impact of "frictional" factors (e.g., long-distances to travel) on voter turn-out. Citizens who are particularly prone to this bias are especially supportive of measures that would increase frictional effects.…”
Section: S-frame Changes That Improve I-frame Decision Making: Helpin...mentioning
confidence: 99%